Rancang Bangun Sistem Informasi Baitulmal “Masjid Jalan Cahaya” Berbasis Website Menggunakan Metode Service Oriented Architecture (SOA): Website-Based Design Of Baitulmal Information System “Masjid Jalan Cahaya” Using Service Oriented Architecture (SOA) Method - Sekarsari Bintang Solehah; Noor Alamsyah; Sri Endang Anjarwani (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2024)
Aside from being a center of worship, the mosque can also function as a place to carry out social muamalah worship. Based on the function, of course the mosque has an agenda or charity activities that are held at certain times. It is the same with the fundraising or crowdfunding system run by Baitulmal